Key factors affecting the pension scheme performance in Albania, and its impact on budgetary deficit, public debt management, and pension levels since the reform measures of 2014-2015 - Stringa, Azmi; Korbi, Alban (Edelweiss Applied Science and Technology, 2025)
The level and sustainability of pensions in Albania have gained increasing attention, particularly in light of rising consumer prices across Europe between 2021 and 2023. The Albanian pension scheme has operated under a persistent deficit, placing strain on public finances. Recognizing this, the government identified pension reform as a strategic priority in its 2014 public financial and debt management frameworks, culminating in the adoption of the Pension Policy Document. This paper analyzes the performance of the pension scheme from 2014 to 2023 using data from the Social Insurance Institute, INSTAT, the Ministry of Finance, the Albanian Supreme Audit Institution, and international sources. It assesses the impact on budget deficits and public debt, and identifies key sustainability factors such as GDP growth, contribution levels, pension benefits, demographic shifts, and labor force participation. Findings reveal that, despite improved revenue collection and tighter control of spending, pension levels have not kept pace with economic growth or inflation, particularly food prices, adversely affecting the elderly. Demographic pressures and limited reform outcomes further challenge sustainability. Practical implications include the need for enhanced fiscal transparency, legal clarity on pension indexation, and the development of a dedicated elderly consumer price index. The study contributes to policy dialogue on pension reform and economic development in transition economies.